When the Inhabitants of Kangiqsujuaq Take a Look at Their Family Photo Albums (1960-2012) - Véronique Antomarchi (Anthropologie et Sociétés, 2015)
This paper presents fieldwork done in July 2012 in the village of Kangiqsujuaq in Nunavik (North Quebec), in the framework of a research project on Inuit imagibility. The project was carried through in agreement with the municipality of Kangiqsujuaq and involved about ten inhabitants who chose to comment some photos from their family albums. The 35 photos chosen by them were scanned and deposited at the Avataq Cultural Institute in Montreal, with the aim of protecting them and to preserve this « ordinary » photographic heritage. The photos have been enlarged and shown as an exhibition in the village so that they can contribute to the transmission between generations of memories of the group as well as families and individuals. The main objective of the project is to take into account the viewpoint of the inhabitants, which will allow to obtain a more appropriate representation of the territory. It remains to be seen whether this small photographic heritage might be integrated into the museographic setting of interpretation centers, such as the centre, situated in this village, of the Pingualuit Park that is presented as the touristic icon of Nunavik. Cet article présente un terrain effectué en juillet 2012 dans un village du Nunavik (Nord Québec) dans le cadre d’un projet sur l’imagibilité inuit. Mené en accord avec la municipalité de Kangiqsujuaq, ce projet a fédéré une dizaine d’habitants qui ont choisi et commenté quelques photos de leurs albums de famille. Les 35 clichés recueillis ont été scannés et déposés à l’Institut culturel inuit Avataq à Montréal en vue d’assurer la protection et la conservation de ce patrimoine photographique « ordinaire ». Ces clichés ont ensuite été agrandis et viennent de faire l’objet d’une exposition dans la communauté afin de permettre la transmission intergénérationnelle autour de la mémoire collective, familiale, individuelle des habitants du village. L’enjeu essentiel de ce projet repose sur la prise en compte du regard des habitants qui permet une représentation plus ...